Strengthening the education sector response to school health, nutrition and HIV/AIDS in the Caribbean region : a rapid survey of 13 countries - O'Connell, Tara (EduCan Christ ChurchBB, 2009)
Aims to inform the development of both regional and national level education sector policies and strategies on school health, nutrition and HIV in the Caribbean region. Aims to describe the current situation of education sector response to these issues and to provide a baseline for monitoring progress and data on the allocation and mobilisation of resources used in such education responses across the region.